IMPLEMENTASI PELAYANAN PERBANKAN MELALUI PROGRAM MAGANG MAHASISWA PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK UNIT LEDO: Penelitian - Oktavianus Giman Giman; Deffrinica Deffrinica (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
This study aims to describe the implementation of banking services through an internship program for students at PT Bank Rakyat Indonesia (Persero) Tbk Unit Ledo. The internship program is conducted as a learning method to provide students with direct work experience in the banking sector. The method used is a participatory approach involving observation, active participation, and documentation. The results show that students are involved in various activities such as customer service, administrative management, document filing, and other operational tasks. This internship provides benefits for students in improving their knowledge, skills, and professional attitude, while also supporting the operational and service activities of the institution. Therefore, the internship program serves as an effective bridge between theoretical knowledge gained in lectures and practical experience in the workplace.